Omnidirectional and broadband photon harvesting in self-organized Ge columnar nanovoids. (23rd July 2022) - Chowdhury, Debasree; Mondal, Shyamal; Secchi, Maria; Giordano, Maria Caterina; Vanzetti, Lia; Barozzi, Mario; Bersani, Massimo; Giubertoni, Damiano; Buatier de Mongeot, Francesco
Abstract: Highly porous Germanium surfaces with uniformly distributed columnar nanovoid structures are fabricated over a large area (wafer scale) by large fluence Sn + irradiation through a thin silicon nitride layer. The latter represents a one-step highly reproducible approach with no material loss to strongly increase photon harvesting into a semiconductor active layer by exploiting the moth-eye antireflection effect. The ion implantation through the nitride cap layer allows fabricating porous nanostructures with high aspect ratio, which can be tailored by varying ion fluence. By comparing the reflectivity of nanoporous Ge films with a flat reference we demonstrate a strong and omnidirectional reduction in the optical reflectivity by a factor of 96% in the selected spectral regions around 960 nm and by a factor of 67.1% averaged over the broad spectral range from 350 to 1800 nm. Such highly anti-reflective nanostructured Ge films prepared over large-areas with a self-organized maskless approach have the potential to impact real world applications aiming at energy harvesting.